Teachers' Perceptions of the Development of Indonesian Language Assessment Guidelines Containing HOTS and Pancasila Student Profiles - Andwina Arum Ratrisari; Subyantoro; Wagiran Wagiran (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Assessment activities are an urgent matter that educational units must carry out. Learning assessment based on Higher-Order Thinking Skills (HOTS) is also an important part of creating the effectiveness of the learning process. HOTS-based assessment is important for the learning process. This is because the results of the critical thinking process are easier to transfer, can understand concepts in depth, and can ultimately be applied to everyday life. The Independent Curriculum frees teachers to make their assessments according to their needs. There is a need for assessment guidelines as a reference for teachers according to the Merdeka curriculum. This research aims to determine how Indonesian language teachers as user practitioners perceive the development of end-of-semester assessment guidelines for class VII Indonesian language subjects containing HOTS and Pancasila student profiles. This research uses a descriptive qualitative research method with data collection techniques originating from a teacher needs questionnaire regarding developing end-of-semester assessment guidelines for class VII Indonesian language subjects containing HOTS and Pancasila student profiles. The results of this research are a description of teachers' perceptions regarding the development of end-of-semester assessment guidelines for class VII Indonesian language subjects containing HOTS and Pancasila student profiles. As a result, 90% of respondents stated that the purpose of this assessment was to measure student learning achievement. The research findings also show that 80% of respondents stated that the development of this assessment was very interesting and useful for learning innovation and could improve students' 21st-century competencies. Apart from that, this research can also be a reference for teachers in carrying out assessment activities according to the Merdeka Belajar curriculum in Middle School Class VII Semester 1 for Indonesian Language Subjects.